Homo deus : a brief history of tomorrow - Harari, Yuval N. (New York, NY : London : Harper, an imprint of HarperCollins Publishers, Penguin, 2017)
Over the past century humankind has managed to do the impossible and rein in famine, plague, and war. For the first time ever, more people die from eating too much than from eating too little; more people die from old age than from infectious diseases; and more people commit suicide than are killed by soldiers, terrorists and criminals put together. The average American is a thousand times more likely to die from binging at McDonald's than from being blown up by Al Qaeda. What then will replace famine, plague, and war at the top of the human agenda? As the self-made gods of planet Earth, what destinies will we set ourselves, and which quests will we undertake? Homo Deus explores the projects, dreams and nightmares that will shape the twenty-first century -- from overcoming death to creating artificial life. It asks the fundamental questions: Where do we go from here? And how will we protect this fragile world from our own destructive powers?
The new human agenda -- Homo sapiens conquers the world. The Anthropocene ; The human spark -- Homo sapiens gives meaning to the world. The storytellers ; The odd couple ; The modern covenant ; The humanist revolution -- Homo sapiens loses control. The time bomb in the laboratory ; The great decoupling ; The ocean of consciousness ; The data religion.
"First published as The History of Tomorrow in Hebrew in Israel in 2015 by Kinneret Zmora-Bitan Dvir. Previously published in Great Britain in 2016 by Harville Secker, a division of Penguin Random House Group Ltd."--Title page verso.
Translation of: ha-Hisṭoryah shel ha-maḥar. 2015.
Includes bibliographical references (pages 403-430) and index.
Keywords: Philosophical anthropology; Human beings -- History; Technological forecasting; Nature -- Effect of human beings on; History, Modern -- 21st century; Science and civilization; Technology and civilization; Civilization, Modern -- 21st century; Civilization, Modern; Human beings; Science and civilization; Technological forecasting; Technology and civilization; History